Women Proprietors of Copyright in England, 1675-1775 - Orr, Leah, (Literature and Cultural Studies E-Books Online, Collection 2026., 2025)
Precision agriculture is a reality in agriculture and is playing a key role as the industry comes to terms with the environment, market forces, quality requirements, traceability, vehicle guidance and crop management. Sensors now in use in agriculture are generating 'Big Data' leading to the use of machine learning and Al - an increasing challenge for agriculture. Research continues to be necessary, and needs to be reported and disseminated to a wide audience. These edited proceedings contain peer reviewed papers presented at the 15th European Conference on Precision Agriculture, held in Barcelona, Spain. The papers reflect the wide range of disciplines that impinge on precision agriculture - technology, crop science, soil science, agronomy, information technology, decision support, remote sensing, data analysis and others. The broad range of research topics reported will be a valuable resource for researchers, advisors, teachers and professionals in agriculture long after the conference has finished.